HUBUNGAN PERAN KELUARGA DENGAN PERILAKU PENCEGAHAN ARTRITIS GOUT PADA LANSIA DI WILAYAH KERJA PUSKESMAS TAPA KEC. TAPA KAB. BONE BOLANGO - Sri Anggun Wahyuni Umar; Hamna Vonny Lasanuddin; Ani Retni (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Arthritis gout, or gout, is an excruciating type of arthritis resulting from metabolism in the body caused by the accumulation of crystals in the joints so that uric acid levels in the body are high. The study aims to determine the relationship between the role of the family and the behavior of preventing arthritis gout in the elderly in the working area of the tapa health center. Type of quantitative method. Desainya Cross Sectional. In this research, there were 50 respondents. Total sampling technique. This collection uses a questionnaire. The results of this study indicate that most respondents have a good family role, as many as 45 respondents (90.00%) and less good five respondents (10.00%) and good prevention behavior 44 respondents (88.00%) and less good six respondents (12.00%). The results of the chi-square statistical test (P-Value = 0.000 <0.05. The role of the family and preventive behavior can be concluded in support so that families can recognize the health problems of family members with arthritis gout and make decisions to take appropriate health actions for their family members. Keywords:, ,